Volatility spillovers and systemic risk across economies: Evidence from a global semi-structural model - Javier G. Gómez-Pineda (Graduate Institute of International and Development Studies, 2018)
The paper presents some evidence on the overwhelming relevance of systemic risk and the lesser importance of US interest rates in the global transmission of shocks. This evidence suggests that the literature could benefit from incorporating global confidence variables into global frameworks in the study of the global transmission of shocks. As framework, we used a global semi-structural model (GSSM) augmented with common factors for country risk and country credit. We approximated country risk with historical stock volatility, a measure that is uniform and available across countries; in addition, we measured spillovers as the share of forecast error variance explained by different volatility factors. We found that systemic risk is the main volatility factor in all systemic economies, and also accounts for the bulk of spillovers into non systemic economies. Other volatility factors such as global credit, foreign interest rates and trade-related factors rarely accounted for shares of forecast error variance above one percent.
Keywords: E58; E37; E43; Q43; 330; Spillovers; Systemic risk; Systemic Economies; Global semi structural model